2000
DOI: 10.1007/s004210000195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance exercise training on mass, strength, and turnover of bone in growing rats

Abstract: To determine the effects of resistance exercise on mass, strength and local turnover of bone, 50 Sprague Dawley rats, 8 weeks of age, were assigned to five groups: a baseline control and two groups of sedentary and exercising rats. The trunk of the rats was kept upright during electrically stimulated jumping exercise for 1 h every other day. In 4 weeks, the trabecular mineralizing surface per bone surface (MS/BS), bone formation rate per bone surface (BFR/BS) and the compression load of the lumbar body increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
85
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 26 publications
18
85
2
2
Order By: Relevance
“…Interestingly, the harmful effect of physical exercise was observed on the femoral breaking energy in the high protein group, while not shown on the BMD. Although voluntary wheel running (17), jumping (18), treadmill running (19) have demonstrated the benefi cial effects of increased load on bone mass or mechanical properties of the femur, tibia, and humerus, the effects of physical exercise were not similar among the different levels of protein intake in our study. Seventy percent of bone strength depends on its density and 30% depends on its quality (20).…”
Section: Discussioncontrasting
confidence: 76%
“…Interestingly, the harmful effect of physical exercise was observed on the femoral breaking energy in the high protein group, while not shown on the BMD. Although voluntary wheel running (17), jumping (18), treadmill running (19) have demonstrated the benefi cial effects of increased load on bone mass or mechanical properties of the femur, tibia, and humerus, the effects of physical exercise were not similar among the different levels of protein intake in our study. Seventy percent of bone strength depends on its density and 30% depends on its quality (20).…”
Section: Discussioncontrasting
confidence: 76%
“…Tamaki et al (30) found running to significantly increase BMD of the femoral diaphysis in OVX rats. In addition, Notomi et al (25) found resistance exercise to significantly increase BMD of the femoral diaphysis in male rats. However, the same effect was not observed with running in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that microarchitectural changes occurred alongside the observed increase in BMD of cancellous bone in the present experiment. On the other hand, varying effects of exercise on the diaphysis have been observed by a number of researchers (25,26,30). Tamaki et al (30) found running to significantly increase BMD of the femoral diaphysis in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7) Animal exercise models are used to examine the preventive or recovery eŠect of exercise on bone mass and strength as endpoints of an experiment. Animal studies using voluntary wheel running, 11) jumping, 12) treadmill running, 13) or voluntary climbing 9,14,15) have demonstrated the beneˆcial eŠect of increased load on bone mass and mechanical properties. Voluntary tower climbing is a light resistance exercise that creates little stress and strain and has been used in several studies.…”
mentioning
confidence: 99%